MODERN METHODOLOGICAL SYSTEM OF THE RHETORICAL COMPETENCE FORMATION OF UNIVERSITY STUDENTS - Natalia Didenko (Scientific Journal of Polonia University, 2023)
The article analyzes the problem of rhetorical competence formation of university students in the process of teaching Ukrainian for special purposes and proposes ways to solve it. Some aspects of the methodological system are proposed. Attention is focused on the peculiarities of students' rhetorical competence formation in the conditions of distance learning, in particular on the use of interactive forms and methods of distance learning, which contribute to the linguistic personality formation of the future specialist. One of the main tasks of higher education is the formation of rhetorical competence of university students. The approaches of scientists to the concepts of “rhetorical competence” and “formation of rhetorical competence” were analyzed and the conditions of rhetorical competence formation in the conditions of distance education were substantiated. It was found that scientific studies consider rhetorical competence as the ability to design effective and optimal communication for the speech situation; to realize one's own rhetorical resources in the process of professional activity, to increase the professional language image. Rhetorical education affects the formation of the language image and the trajectory of the professional career of the future specialist. Rhetorical competence involves the formation of personal qualities, the development of thinking, speech, the ability to conduct business communication according to the rules of etiquette. The process of rhetorical competence formation requires updating the methodical system, building the specifics of practical classes in the conditions of a distance learning mode and the complex realities of wartime in Ukraine.